ANTIBACTERIAL ACTIVITY CAMBODIA LEAF EXTRACT (Plumeria alba L.) to Staphylococcus aureus AND IDENTIFICATION OF BIOACTIVE COMPOUND GROUP OF CAMBODIA LEAF EXTRACT - Dian Riana Ningsih; Zusfahair Zusfahair; Purwati Purwati (Universitas Jenderal Soedirman, 2014)
A wide variety of flora can be found and can be used, as a medicinal plant. Medicinal plants are a majorsource of new chemical compounds discovery with therapeutic effects. One of the plants that can be used as a medicinal plant is a cambodia plant (Plumeria alba L cv. Acutifolia). Cambodia plants including theApocynaceae family. Cambodia is a traditional crop plants that are reported to have various properties,including its leaves as a laxative, itching and antibacterial, fruit and bark reported anti-inflammatory effect.The purpose of this study was to determine the potential of cambodia leaves as antibacterial, determining the Minimum Inhibitory Concentration Growth (KHTM) of cambodia leaf extract which has the highest inhibitoryactivity and determine what class of chemical compounds contained in extracts of cambodia leaves which hasthe highest antibacterial activity . Research results showed that the leaf extract of cambodia leaves with 1000 ppm can inhibit the growth of S. aureus bacteria. Concentration of 30 ppm is the lowest concentration thatcould inhibit the growth of S. aureus with inhibition zone of 1.3 mm. Analysis of FT-IR spectrophotometer,the ethanol leaves extract of the cambodia have functional group of C-H sp3 (methyl) (methyl), C-C, C = Calkenes aliphatic, OH and CO.